(3QSGdI TQjYI Cgd GdjghO hGdLMhO CYfi GdcaQI ef Cgd TQjYI GdjghOs - (3MeRI Hf Ydj Hf CMeO GdaGQSqj GdMGcej GdOQRj , J (B433 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdMGce hMOg hJhSdJ Edjg HbGFe GdMb YHOg CeG HYO aGdMeO ddehdi GdMGce GdefRg Yf JfRjg GdCfGe GdeJYGdi Yf YHGOg GdCdSf s
(3BNQgG (B:s
(3hbO HdZfG GdZQV hCOjJ MbjbI GdeaJQV adfNJe Pdc HGdMeO ddHGQ GdefRg Yf GdYOe hGdTcQ dhdjg gGOi GdCee JeJ Hefg hdi GdCeQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B71s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds